2016
DOI: 10.1103/physrevlett.117.133603
|View full text |Cite
|
Sign up to set email alerts
|

Large Bragg Reflection from One-Dimensional Chains of Trapped Atoms Near a Nanoscale Waveguide

Abstract: We report experimental observations of a large Bragg reflection from arrays of cold atoms trapped near a one-dimensional nanoscale waveguide. By using an optical lattice in the evanescent field surrounding a nanofiber with a period nearly commensurate with the resonant wavelength, we observe a reflectance of up to 75% for the guided mode. Each atom behaves as a partially reflecting mirror and an ordered chain of about 2000 atoms is sufficient to realize an efficient Bragg mirror. Measurements of the reflection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 44 publications
5
172
0
Order By: Relevance
“…There is a revival of the reflectivity about 4 ”s after the structure pulse, showing a brief re-phasing of some of the pumped atoms oscillating in the trap. Corzo et al (2016) also report Bragg reflection from atoms trapped on a nanofiber. By using an optical lattice with a period nearly commensurate with the resonant wavelength, realized by a pair of close-to-resonance red-detuned counterpropagating beams, they observe a reflectance of up to 75%.…”
Section: Reflectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…There is a revival of the reflectivity about 4 ”s after the structure pulse, showing a brief re-phasing of some of the pumped atoms oscillating in the trap. Corzo et al (2016) also report Bragg reflection from atoms trapped on a nanofiber. By using an optical lattice with a period nearly commensurate with the resonant wavelength, realized by a pair of close-to-resonance red-detuned counterpropagating beams, they observe a reflectance of up to 75%.…”
Section: Reflectivitymentioning
confidence: 99%
“…1 (not to scale), are another example of this kind of structure. It has been demonstrated that ONFs provide an excellent platform to interface trapped atoms to the evanescent field of the mode around a nanometer-size waist region ; Goban et al (2012); BĂ©guin et al (2014); Lee et al (2015); Kato and Aoki (2015); Corzo et al (2016). We review the platform of ONFs with atoms and their implications and applications for quantum physics.…”
Section: Cooperativity and Optical Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…Such lightmatter interfaces have enabled a number of advancements in sensing and quantum information science. For example, ultracold atoms have been trapped and manipulated in evanescent fields of single-mode optical nanofibers for single-photon switches and ultralow power nonlinear optics [1][2][3][4][5]. The strength of the atom-photon interaction depends critically on the waveguide dimensions, and optimization of the light-matter interaction requires exquisite control of the evanescent field by tailoring the precise geometry of the waveguide [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These waveguides have enabled several advances in quantum information technologies, including optical switches [8] and atom-mediated optical isolators [9,10], but have also facilitated fundamental experiments in nonlinear atom-light interactions [11], atom-number-resolving detection [12], electromagnetically induced transparency [13][14][15][16], and Bragg reflection from atoms [17,18].…”
Section: Introductionmentioning
confidence: 99%